Use of CAD/CAM in Esthetic Restoration of Badly Decayed Tooth - Satheesh B. Haralur; Ali Hassan Al-Faifi (Case Reports in Dentistry)
Proper, intelligent use of materials and technology should be utilized for the benefit of the patient. This case report presents a patient with a badly broken premolar tooth demanding high esthetic all-ceramic restoration. Following multiple procedure tooth was restored with zirconia all ceramic restoration. Multiple procedures to save a tooth are a really worthy, in the interest of patients. Use of zirconia and CAD-CAM will help in saving many compromised tooth even in high-stress regions. This provides the patient a chance to have restorations, which are biomechanically superior in addition to being pleasing esthetically.